Analisis Faktor Internal dan Eksternal Perusahaan terhadap Penurunan Pengiriman Barang Kargo di PT. Lintas Maju Nusantara - Dian Lestari; Resista Vikaliana (LPPM Universitas Jambi, 2021)
PT Lintas Maju Nusantara is one of the cargo delivery companies in Bekasi City. In the latest period, there has been a significant decline in cargo shipments. This research was conducted with the aim of knowing the internal and external factors that caused the decline in shipments, and ways to overcome the decline. This research focused on internal factors which include facilities, services, marketing, and employees of PT Lintas Maju Nusantara, and external factors which include competitors, customers, and government regulations. The research method used was quasi-qualitative with data collection techniques in the form of interviews, observation, and documentation. The results of this study indicate that the facilities owned by the company still require attention. On the other hand competitors and government regulations have also become a strong factor in the decline in cargo shipments that occurred at PT Lintas Maju Nusantara.